FR2.3: Even the Goats Feel the Heat: Gender, Livestock Rearing, Rangeland Cultivation, and Climate Change Adaptation in Tunisia - Najjar, Dina (International Center for Agricultural Research in the Dry Areas, 2022)
Women's contributions to rangeland cultivation in Tunisia and the effects of climate change upon their livelihoods are both policy blind spots. To make women's contributions to rangeland cultivation more visible and to provide policy inputs based on women's needs and priorities into the reforms currently being made in Tunisia, we conducted fieldwork in three governorates. We conducted focus groups and interviews with a total of 289 individuals. We found that men and women are negatively affected by rangeland degradation and water scarcity, but women are additionally disadvantaged by their inability to own land and access credit, and by drought-mitigation and rangeland rehabilitation training that only target men. Our findings reveal that women are involved in livestock grazing and rearing activities to a greater extent than is widely assumed, but in different ways than the men in the same households and communities. Understanding how women use rangelands is a necessary first step to ensuring that they benefit from rangeland management at par with men. Women's feedback and priorities should be considered critical for the sustainable and equitable use and management of rangelands. Women's growing involvement in livestock rearing and agricultural production must be supported with commensurate social and economic policy interventions. As an example, it is crucial that women gain access to drought management and adaptation training at par with men. Providing male and female farmers with appropriate supports to optimize rangeland cultivation and productivity is particularly urgent and important in the context of resource degradation accelerated by climate change.